Efficiency of application of the “Shuttle time” program for increasing the technical and tactical situation of students-badmintonists. (Journal of Educational Sciences, 2022)
The article deals with the technical and tactical training of athletes-badminton, who are studying in the first year of the university, using the Asian program "Shuttle Time". ”. The "Shuttle Time" program was compiled by Asian educators and is being implemented in countries where badminton is not so popular as throughout Europe, China, Indonesia, Malaysia, etc. The article analyzes the results of tests to check the technical and tactical training of students in the experimental and control groups. The training activity of student-athletes in the control group is carried out by traditional methods, and in the experimental group the Asian program is used. Also, the results determine the significance of the "Shuttle Time" program itself. The expediency of using this program shows the results that make it possible to use it in further practical and competitive activities. This article presents the results of tests to determine the technical and tactical training of athletes, specializing in badminton, using the "Shuttle Time" program. The tests were carried out in three stages, with a frequency of five months. The subjects passed four tests to check their technical and tactical training. The relevance of the article is the use of technical and tactical abilities during the training process using the "Shuttle Time" program. This article proves the influence of the "Shuttle Time" program on improving the technical and tactical training of badminton players and the effectiveness of its use in the training process. The possibility of the proposed program in the future to use skills in competitive activities.Keywords: tactical training, technical training, badminton, “Shuttle Time”.